Cultural congruence or compensation? A meta-analytic test of transformational and transactional leadership effects across cultures - Rockstuhl, Thomas; Wu, Dongyuan; Dulebohn, James H.; Liao, Chenwei; Hoch, Julia E. (Journal of International Business Studies, 2023)
Prior research is equivocal about whether leadership is more effective when it matches typical cultural practices (the cultural congruence argument) or compensates for "ineffective" cultural practices (the cultural compensation argument). We propose that a more nuanced answer to the congruence-versus-compensation debate requires the joint consideration of leadership, culture, and task contexts. A meta-analysis of 460 field samples of transformational leadership (N = 124,646) and 139 field samples of transactional leadership (N = 38,327) across 53 cultures revealed three key results: First, both transformational and transactional leadership universally relate positively to follower performance outcomes. The strength of these relationships ranges between 0.25 and 0.39 for transformational leadership and between 0.12 and 0.24 for transactional leadership. Second, the positive effects of transformational leadership on convergent performance outcomes are more pronounced in cultures characterized by norms of vertical differentiation (including high power distance) and harmony (including collectivism), consistent with the cultural congruence perspective. Third, the positive effects of transactional leadership on divergent performance outcomes are more pronounced in cultures characterized by norms of low performance-focus (including low uncertainty avoidance), consistent with the cultural compensation perspective. We discuss the implications of these findings for transformational and transactional leadership research and practice.